A lack of α1A-adrenergic receptor-mediated antidepressant-like effects of S-(+)-niguldipine and B8805-033 in the forced swim test. Issue 4 (June 2016) - Kreiner, Grzegorz; Roman, Adam; Zelek-Molik, Agnieszka; Kowalska, Marta; Nalepa, Irena
Abstract : The α1 -adrenergic receptors (α1 -ARs), which belong to a G protein-coupled receptor family, consist of three highly homologous subtypes known as α1A -ARs, α1B -ARs, and α1D -ARs. Our previous findings suggested that α1A -ARs are an important target for imipramine and electroconvulsive therapy. The current study sought to evaluate whether S -(+)-niguldipine and B8805-033, two selective antagonists of α1A -ARs, can evoke antidepressant-like effects in the forced swim test in rats. Both compounds were administered at three time points (24, 5, and 1 h before testing), and the effects of three doses (2, 5, and 10 mg/kg) of each compound were investigated. S -(+)-Niguldipine produced no antidepressant-like effects other than a 14% reduction in immobility time at the highest dose. Although B8805-033 at a dose of 2 mg/kg did not influence the rats' behavior, higher B8805-033 doses (5 and 10 mg/kg) produced significant reductions in immobility time (approximately 42 and 44% vs. controls, respectively; P <0.01). However, this effect was abolished by the concomitant administration of WAY100135, a serotonin receptor antagonist, suggesting that the observed antidepressant-like effects of B8805-033 are unrelated to α1A -ARs. Nevertheless, given the current dearth of selective α1A -AR agonists, the question of whether this particular subtype could be involved in antidepressant therapy mechanisms remains unresolved.